Submandibular gland sialolith - Md Shahjahan Ali; Md Mahfuz Hossain; Ashim Kumar Saha; Md Harun-ur Rashid; Md Nazmul Hasan (Update Dental College, 2013)
Sialolithiasis is the most common salivary gland disease, occurs most commonly in middle aged patient. There is a slight male predominance. More than 80% of salivary calculi occur in the submandibular glands or its duct. It is estimated that sialolithiasis affect 12 of every 1000 patients in the adult population. It is believed that deposition of mineral salts around a nidus of bacteria, mucous, or desquamated cells develops a salivary calculi. The possible aetiological factors for salivary calculi formation are salivary stagnation, increased alkalinity of the saliva, increased calcium content of the saliva, infection or inflammation, or physical trauma of the salivary duct or gland. The submandibular gland is most susceptible for sialolith formation because its saliva is more alkaline,has a higher mucus content,has a greater concentration of calcium and phosphate, has a longer and irregular duct, has antigravity flow. Here report a case of middle aged female patient with sialolith in right submandibular gland successfully treated with surgical removal of the gland containing sialolith. DOI: http://dx.doi.org/10.3329/updcj.v2i2.15536 Update Dent. Coll. j: 2012; 2 (2): 47-50